OSA and cardiometabolic risk: What's the bottom line?. Issue 3 (5th February 2017) - Hoyos, Camilla M.; Drager, Luciano F.; Patel, Sanjay R.
ABSTRACT: Obstructive sleep apnoea (OSA) is a common condition characterized by repetitive upper airway obstruction during sleep. OSA promotes wide intrathoracic pressure swings, intermittent hypoxia and sleep fragmentation. Growing evidence derived from animal models mimicking the oxygen profile observed in patients with OSA as well as clinical studies support that this important sleep‐disordered breathing is associated with increased cardiovascular risk. Although the precise mechanisms are not fully established, it is conceivable that the metabolic deregulation promoted by the components of OSA may have an important causal role in the poor cardiovascular prognosis. In this review, we summarize the potential role of OSA and its components on cardiometabolic disease. We also summarize evidence evaluating the impact of OSA treatment (notably continuous positive airway pressure) on reversing the metabolic deregulation promoted by OSA. Finally, we discuss the research agenda and perspectives for this important research area.